Optimization of Motor Vehicle Tax Revenue through the Superior SAMSAT Program at UPT Revenue Maros - Sakir, Ahmad Rosandi; Mustari, Sri Hariati (Jurnal Magister Administrasi Publik, 2021)
Tax is a mandatory contribution to the state that is owned by an individual or entity that is coercive in nature based on the law, with no direct compensation and is used for the needs of the state for the greatest prosperity of the people. Tax is one of the main sources of revenue for a country that is paid by the public. Taxes are also levies that can be levied by the government based on the provisions of tax laws and regulations and as a form of public participation for taxpayers to directly and jointly carry out tax obligations needed for state financing and national development. One source of Regional Revenue comes from Motor Vehicle Tax (PKB). Motor vehicle tax has an important role in regional development, so it is appropriate for every individual or community owner of motorized vehicles to comply and timely pay taxes in accordance with the law to facilitate programs and activities that have been planned by the regional government. The research method used is deductive qualitative. Respondents are the heads of the Maros Revenue Service and taxpayers. The results of the study explain that the very good Samsat Program is very well felt by the community because, in addition to facilitating the service process, it also brings the community closer to the service process for Payment of Motor Vehicle Taxes. The Samsat Unggul program includes activities for Samsat Outlets and Shops, Mobile Samsat, and Door To Door.